ADULTERY CHILD STATUS IN ISLAMIC LAW AND IN THE CIVIL CODE - HARI SUTRA DISEMADI (Hukum Islam, 2019)
Problems regarding the status of children born outside of legal marital relations are still interesting discussions. In the community the status of children is often questioned, because not a few children are born without marriage. So from this this study will focus on the status of illegitimate children in Islamic law and in the Civil Code. The research method used is a normative juridical research method based on secondary data, namely primary legal material, secondary legal material and tertiary legal material. This research shows that in Islamic law and Civil Code the legitimate denial of children can result in the breakup of marriage making the child an illegitimate child and not having an inheritance relationship with his parents, but his mother according to Islamic law. If the child of adultery is associated with obligations and responsibilities regarding survival, then the parents or fathers are still charged with the obligation to provide a living. As the cost of living and the cost of their education as needed or according to their abilities, because he is the biological father of the child. If the status of the adultery child is associated with inheritance according to BW, then he does not inherit at all to the two tunya people. but if it is associated with Islamic inheritance, then he inherits only his mother and his mother's family.